RBF-NN-based model for prediction of weld bead geometry in Shielded Metal Arc Welding (SMAW) - Ahmed A.N.; Noor C.W.M.; Allawi M.F.; El-Shafie A. (Springer London, 2023)
Artificial intelligence; Carbon steel; Electric arc welding; Forecasting; Gas metal arc welding; Geometry; Neural networks; Radial basis function networks; Repair; Steel research; Welding; Welds; Artificial intelligence techniques; Multilayer perceptron neural networks; Physical characteristics; Prediction model; Radial basis function neural networks; RBF-NN; Shielded metal arc welding; Welding process; Electric welding